2010
DOI: 10.3748/wjg.v16.i33.4193
|View full text |Cite
|
Sign up to set email alerts
|

Effect ofArctium lappaL. in the dextran sulfate sodium colitis mouse model

Abstract: We suggest that AL can prevent intestinal damage and decrease inflammatory cytokines in mice with DSS-induced colitis. Thus, AL could prove to be a useful food for UC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
29
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 22 publications
9
29
0
1
Order By: Relevance
“…It is well known that the percentage of DSS exposure and colony of animal closely relate to the success of the UC model (Elvington et al , ; Johswich et al , ; Wang et al , ). Commonly, a higher percentage (5%, w / v ) of DSS is employed to establish an acute UC model, to elicit serious colon injury (Huang et al , ; Wadie et al , ; Wang et al , ). In the present study, Sprague–Dawley rats were given drinking water containing 5% ( w / v ) DSS ad libitum for 7 days to induce acute colitis, and on day 4, the majority of rats exposed to DSS presented with serious mucopurulent stool (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that the percentage of DSS exposure and colony of animal closely relate to the success of the UC model (Elvington et al , ; Johswich et al , ; Wang et al , ). Commonly, a higher percentage (5%, w / v ) of DSS is employed to establish an acute UC model, to elicit serious colon injury (Huang et al , ; Wadie et al , ; Wang et al , ). In the present study, Sprague–Dawley rats were given drinking water containing 5% ( w / v ) DSS ad libitum for 7 days to induce acute colitis, and on day 4, the majority of rats exposed to DSS presented with serious mucopurulent stool (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Using this model, we found that W. chinensis could effectively attenuate specific clinical symptoms and provide protection against the histopathological changes caused by colonic inflammation. Previous studies have shown that specific medicinal herbs, such as Arctium lappa (burdock) and Scutelleria baicalensis , can confer anti-colitis activities [34], [35]. Comparison with results from these studies suggested that WCHF extract from W. chinensis had a considerably lower effective dosage (e.g., 50, 100 and 1000 mg/kg for W. chinensis , A. lappa and S. baicalensis , respectively) than the previously tested medicinal plants [34], [35].…”
Section: Discussionmentioning
confidence: 99%
“…Fructus arctii have been reported to have antimicrobial, antioxidant, and anti-inflammatory activities (Lin et al, 1996;Huang et al, 2010). Research on the chemical compositions of Fructus arctii has shown that the most active ingredient of Fructus arctii is arctigenin (C 21 H 24 O 6 with a molecular weight of 372.41), a phenylpropanoid dibenzylbutyrolactone lignan (Hirose et al, 2000;Cho et al, 2004;Huang et al, 2004).…”
Section: Introductionmentioning
confidence: 99%